The relationship between psychosocial factors and biomarkers in cancer patients: A systematic review of the literature. (August 2019) - Cheng, Lin; Meiser, Bettina
Abstract: Purpose: This review measured the relationships between psychosocial factors and biomarkers in cancer research setting in order to summarize their relationship. It may help to clarify the roles of psychosocial factors and biomarkers in cancer treatment, provide information for developing interventions, and contribute to personalized medicine. Methods: A total of 4 databases were searched and 2151 articles were screened. Thirty eligible articles were captured including 2093 cancer patients with 11 different kinds of tumor. Results: Totally 10 groups of biomarkers, 7 positive and 7 negative psychosocial factors were identified. Higher scores of positive psychosocial factors and lower scores of negative psychosocial factors were associated with biomarkers indicating good clinical results. Tumor types can affect the significance of results. Interactions among psychosocial factors may influence the main effect of the targeted psychosocial factors. Biomarkers in reviewed studies were immune response-related biomarkers. Conclusions: The identified psychosocial factors may provide information for intervention development to increase the quality of life of cancer patients during their cancer treatment and promote better clinical outcomes. When investigating the relationship between psychosocial factors and biomarkers, the tumor type and interaction among psychosocial factors should be noted. Highlights: Totally 10 groups of biomarkers and 14 psychosocial factors were identified. Psychosocial factors were associated with biomarkers indicating clinical results. Tumor types can affect the significance of results. Interactions among psychosocial factors may influence. Results from various tumor types are needed.